Analysis of the Ability of Leading Teachers in Developing Themselves as Principals at Sukadamai Elementary School, Aceh Besar - Syahri, Rika; Khausar, Khausar; Akmaluddin, Akmaluddin (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The purpose of this study is to describe and analyze the ability of the driving teacher in developing himself as a principal at Sukadamai Elementary School, Aceh Besar. The research method is qualitative with a descriptive type. The research informants consist of the principal, subject teachers, curriculum team leaders and education staff. Data collection uses interviews, observation and documentation and analysis is descriptive qualitative. The results of the study indicate that the driving teacher in developing himself as a principal at Sukadamai Elementary School, Aceh Besar has the ability to lead his school effectively, innovatively, and student-centered, so that he is able to bring positive changes in the school environment and improve the quality of education at Sukadamai Elementary School, Aceh Besar. The ability of the principal who has a background as a driving teacher at Sukadamai Elementary School is seen from the aspects of leadership skills, collaboration and innovation that have been developed, self-development, learning development and improving the quality of education in the school he leads.